Предмет: Математика,
автор: ghost467
10*х-(х+5) при х=-10
Ответы
Автор ответа:
2
10х - (х+5)=10х-х-5=9х-5=9*(-10)-5=-90-5=-95
Автор ответа:
1
10х - (х+5) при х = -10.
Решение:
10х - (х+5) = 10х - х - 5.
если х = -10, то 10х - х - 5 = 10 * (-10) - (-10) - 5 = -100 + 10 - 5 = -90 - 5 = -95.
Похожие вопросы
Предмет: Математика,
автор: katrinee662
Предмет: Английский язык,
автор: realrichbaby
Предмет: Геометрия,
автор: maviandcookiei
Предмет: Математика,
автор: number7seven
Предмет: Математика,
автор: лина385